Global Comparative Study on REDD+ story of change: CIFOR’s science on wetlands for Indonesian measurement, reporting and verification and forest reference emission level development - Bhomia, R.K.; Nofyanza, S.; Thürer, T.; O’Connell, E.; Murdiyarso, D. (Center for International Forestry Research, 2021)
Tropical forested wetlands, including peatlands and mangroves, provide critical environmental services and store 3–5 times more carbon than other tropical forests. However, because these ecosystems are under significant pressure from unsustainable land-use practices, they must be credited in the national forest monitoring and measurement mechanism and integrated into the national policy agenda